2010
DOI: 10.1007/s11605-010-1280-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Volume Versus Morbidity and Cost in Patients Undergoing Pancreaticoduodenectomy in an Academic Community Medical Center

Abstract: Surgeon volume and patient body mass index have a significant impact on perioperative morbidity following PD in a community teaching hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…Despite that our overall duration of stay could seem longer than those described by others, 31,43,63,64 especially by US centers, 65,66 immediate postoperative outcomes in group 14p invasion were identical or easier than others, as evidenced by comparable mean duration of stay (21 vs 23 days) or absence of grade IV/V complications. Despite that our overall duration of stay could seem longer than those described by others, 31,43,63,64 especially by US centers, 65,66 immediate postoperative outcomes in group 14p invasion were identical or easier than others, as evidenced by comparable mean duration of stay (21 vs 23 days) or absence of grade IV/V complications.…”
Section: Discussioncontrasting
confidence: 49%
“…Despite that our overall duration of stay could seem longer than those described by others, 31,43,63,64 especially by US centers, 65,66 immediate postoperative outcomes in group 14p invasion were identical or easier than others, as evidenced by comparable mean duration of stay (21 vs 23 days) or absence of grade IV/V complications. Despite that our overall duration of stay could seem longer than those described by others, 31,43,63,64 especially by US centers, 65,66 immediate postoperative outcomes in group 14p invasion were identical or easier than others, as evidenced by comparable mean duration of stay (21 vs 23 days) or absence of grade IV/V complications.…”
Section: Discussioncontrasting
confidence: 49%
“…Previous studies showed the relationship between high hospital‐volume and surgeon‐volume on a lower incidence of complications and quality of care . It seems fair to say that cost savings can be achieved nation‐wide by performing pancreatic surgery only in high‐volume hospitals and by experienced surgeons …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed the relationship between high hospital-volume and surgeon-volume on a lower incidence of complications and quality of care. 11,[39][40][41] It seems fair to say that cost savings can be achieved nation-wide by performing pancreatic surgery only in high-volume hospitals and by experienced surgeons. 21 The overall complication rate in the present study was higher than in previous reports from our hospital as well as from other contemporary studies despite a 1% mortality.…”
Section: Hpbmentioning
confidence: 99%
“…Multiple previous studies have demonstrated that increased procedure volume leads to a dramatic decrease in perioperative mortality. 2226 Specifically, Kennedy et al 22 found that high-volume PD surgeons have better outcomes including complication rates and overall mortality. In the current study, we also noted that in-hospital and 90-day mortality were higher among lower-volume hospitals and surgeons.…”
Section: Discussionmentioning
confidence: 99%